Legal Education In The Context Of Legal Practice - Norfadhilah Mohamad Ali; Al’Uyuna; Mohd Amin; Marsita Md Nor; Mohd Hazmi Mohd Rusli; Syahirah Abdul Shukor; Mohd Nasir Abd Majid; Hendun Abd. Rahman Shah; Lukman Abdul Mutalib; Ahmad Zaki Salleh (Science Publishing Corporation, 2024)
International Journal of Engineering & Technology, Volume 7 Issue 2.29 Page (494-497)